2021
DOI: 10.1016/j.adaj.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dental care use patterns due to COVID-19 among insured patients in the United States

Abstract: Background Demand for dental services has been known to be closely linked to dental insurance and disposable income. Widespread economic uncertainty and health systems changes due to the coronavirus disease 2019 (COVID-19) thus may have a significant impact on dental utilization. Methods Using de-identified dental practice management data in 2019 and 2020, we observed variations in dental utilization among insured patients since the COVID-19 outbreak (during the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 11 publications
4
25
1
2
Order By: Relevance
“…28 Results of analysis of practice management data found that oral health care use has fully rebounded to prepandemic levels among privately insured patients. 29 These later studies, indicating adaptation to new safety procedures and rebounding dental demand, are consistent with our optimistic findings.…”
Section: Discussionsupporting
confidence: 90%
“…28 Results of analysis of practice management data found that oral health care use has fully rebounded to prepandemic levels among privately insured patients. 29 These later studies, indicating adaptation to new safety procedures and rebounding dental demand, are consistent with our optimistic findings.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies showed that the COVID-19 pandemic resulted in substantial decrease in procedure volume for patients covered by public insurances in the United States ( 16 ). There are other socioeconomic factors that could contribute to patients’ behavior in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The following sociodemographic characteristics, health-related behaviors, and health status were included in the model as covariates: age, sex, self-rated health (great, good, not bad, and bad), regular dental visit (at least once a year, at least once every 2–3 y, almost never went, and never went), and employment status (full-time employee, part-time employee or other, not working). The covariates included in this study were based on previous evidence on age (Koyama and Takeuchi 2020; Choi, Simon, Basu, et al 2021; Meisha et al 2021), sex (Thompson et al 2016; Koyama and Takeuchi 2020; Meisha et al 2021), self-rated health (Brennan and Teusner 2015), regular dental visits (Koyama and Takeuchi 2020; Meisha et al 2021), and employment status (Meisha et al 2021).…”
Section: Methodsmentioning
confidence: 99%